Legal Literacy: The Role of Housewives in Overcoming Phising Criminal - Ismiati, Chusnur; Borman, Muhammad Syahrul; Handoko Putro, Guruh Marhaenis (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2024)
The rise of fraudulent methods seems to be a big task for state officials in Indonesia. Housewives are the primary victims of phishing crimes. The absence of knowledge and information about legal literacy in relation to phishing crimes via WhatsApp and Telegram messages appears to be a significant obstacle. This study aims to understand the role of housewives in Surabaya, particularly in dealing with phishing, and educate their family and friends about legal literacy to prevent them from becoming victims of these criminal acts. We use a descriptive method that employs a quantitative approach. The data used is primary data. The data collection technique entails distributing data via a Google Form questionnaire and utilizing information from previous literature, journals, online media, and books. The research results showed that messages sent via WhatsApp or cellphones, which contained invitations to join or clicked on unclear links, had the greatest impact on the group of elderly housewives. This is due to a lack of information regarding fraud prevention awareness. Housewives are required to be socialized about phishing crimes and legal literacy. Legal literacy among housewives in the city of Surabaya is very necessary, considering that there are many cases of violations committed by housewives, some of which even have criminal consequences. Educating housewives on the fundamentals of fair legal literacy can help lower the high crime rate that stems from a lack of legal understanding. The elderly group, especially housewives in Surabaya, still lacks experience dealing with personal problems based on their comfort.